2021
DOI: 10.3390/ijerph18179355
|View full text |Cite
|
Sign up to set email alerts
|

Poor Health Related Quality of Life and Unhealthy Lifestyle Habits in Weight-Loss Treatment-Seeking Youth

Abstract: Obesity is associated with unhealthy lifestyle behaviors and poor Health Related Quality of Life (HRQOL). The cumulative effect of lifestyle behaviors on HRQOL has been demonstrated in chronically ill adolescents, but not in adolescents with obesity. The present study aimed to assess the association between HRQOL and adherence to the Mediterranean Diet (MD) and/or low levels of physical activity (PA) in a large sample of outpatient adolescents with overweight or obesity seeking weight loss treatment. Four-hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Of the eight studies that reported the value of the correlation with the HRQoL general score, four [ 14 17 ] showed positive associations of MD adherence with higher levels of HRQoL with statistically significant values; the β-value ranged from 0.13 to 0.26. In contrast, the study that evaluated the OR [ 24 ] reported a value of 0.878 (95% CI, 0.804–0.959) between better MD adherence and high/intermediate HRQoL (for each increase in one unit of the KIDMED score, the odds of "low total functioning" will decrease by 12%). Of the other three studies with no statistically significant results, two found a positive association, and one found a negative association between MD and HRQoL.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the eight studies that reported the value of the correlation with the HRQoL general score, four [ 14 17 ] showed positive associations of MD adherence with higher levels of HRQoL with statistically significant values; the β-value ranged from 0.13 to 0.26. In contrast, the study that evaluated the OR [ 24 ] reported a value of 0.878 (95% CI, 0.804–0.959) between better MD adherence and high/intermediate HRQoL (for each increase in one unit of the KIDMED score, the odds of "low total functioning" will decrease by 12%). Of the other three studies with no statistically significant results, two found a positive association, and one found a negative association between MD and HRQoL.…”
Section: Resultsmentioning
confidence: 99%
“…After full-text revision of 28 articles, 17 articles were excluded because of the following: they included neither MD nor HRQoL ( n = 4), the association between QoL and the MD was not investigated ( n = 6), the publication of another study was already included ( n = 2), there were statistical inconsistencies ( n = 4) and there was one study in which HRQoL presented a value that was not plausible (see Additional File 2 ). Finally, 11 articles were included for qualitative synthesis [ 14 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations